Proses Penyelesaian dan Hambatan-Hambatan yang Dihadapi dalam Pemberian Sanksi Adat terhadap Perbuatan La’a Sala (Incest) di Desa Ulu Belu, Kecamatan Golewa, Kabupaten Ngada - Maximilianus Aldo Ame Ola; Rudepel Petrus Leo; Bhisa V. Wilhelmus (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Incest is a sexual relationship carried out by two people who are still related by blood or marriage. Incest is described as an incident of sexual intercourse; between individuals who are related by blood, but the term was eventually used more broadly, namely to describe the sexual relationship between father and child, between siblings. Incest is a forbidden act in almost every cultural environment. The main problems in this thesis are: (1) What is the resolution process in providing customary sanctions for acts of la'a sala (incest) in Ulu Belu Village, Golewa District, Ngada Regency? (2) What are the obstacles faced in providing customary sanctions for acts of la'a sala (incest) in Ulu Belu Village, Golewa District, Ngada Regency? This research is empirical normative research, so the data sources used are primary data sources, secondary data and tertiary data. Primary data was obtained from interviews, secondary data was obtained from libraries, journals and the internet, and tertiary data was obtained from dictionaries, Wikipedia and encyclopedias. Data were analyzed descriptively-qualitatively. The results of this research show that (1) The process of resolving cases of granting customary sanctions for acts of la'a sala (incest) was carried out in a non-litigation manner which was accommodated and chaired directly by Mosa and the traditional leader in Ulu Belu village in accordance with the customary rules. applies. (2) the obstacles faced in providing customary sanctions for acts of la'a sala (incest) are external obstacles and internal obstacles.